Pluralisme: Tantangan dan Peluang dalam Proses Dakwah Islam Kontemporer - Abdul Hamid (AL-BAYAN INSTITUTE, 2023)
Indonesia is a pluralistic country with a diversity of tribes, races, cultures, and religions. This diversity is known as plurality and is legally recognized through the motto